Impact of Connective Tissue Disease on Oncologic Breast Surgery and Reconstruction. Issue 6 (June 2016) - Shuck, John; Patel, Ketan M; Franklin, Brenton; Fan, Ken L.; Hannan, Lindsay; Nahabedian, Maurice Y.
Abstract : Background: The impact of connective tissue disease (CTD) on outcomes following breast surgery and reconstruction is unknown. The purpose of this study was to evaluate the effect of both CTDs and systemic immunomodulatory therapy on outcomes following breast surgery and reconstruction. Methods: A retrospective review was performed of all patients from 2005 to 2010 with an active CTD who underwent breast surgery with or without reconstruction. Surgical events were assigned to 1 of 4 groups: ablative surgery alone, autologous reconstruction, implant reconstruction, and revision surgery. Logistic regression was utilized to examine the relationship between complications and type of surgery, CTD diagnosis, and immunomodulatory therapy. Four non-CTD control groups were then compiled for outcome comparison. The a priori P -value was set at P < 0.05, and all tests were 2 sided. Results: Thirty-three patients with CTD underwent112 procedures. Diagnoses included psoriasis/psoriatic arthritis (n = 12), rheumatoid arthritis (n = 10), lupus (n = 4), scleroderma (n = 3), Sjogren syndrome (n = 2), mixed CTD (n = 1), and seronegative polyarthritis (n = 1). Nineteen of 33 (58%) patients who received systemic treatment for CTD in the perioperative period were less likely to experience a minor complication compared with those without treatment (odds ratio= 0.69; P = 0.019). There were no differences in postoperative complications in patients with CTD compared with control groups. Conclusions: Ablative breast surgery and reconstruction among patients with CTDs can be performed safely with low perioperative complication rates. Patients receiving systemic therapy, and continuing their regimens perioperatively, experience complication rates similar to those not requiring therapy.